2023
DOI: 10.3390/molecules28114357
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation in Infectious Diseases and Its Potential as a Biosensor in Future Aquaculture Industry: A Review

Aileen See SiouNing,
Tang Swee Seong,
Hidehiro Kondo
et al.

Abstract: An infectious disease is the most apprehensive problem in aquaculture as it can lead to high mortality in aquatic organisms and massive economic loss. Even though significant progress has been accomplished in therapeutic, prevention, and diagnostic using several potential technologies, more robust inventions and breakthroughs should be achieved to control the spread of infectious diseases. MicroRNA (miRNA) is an endogenous small non-coding RNA that post-transcriptionally regulates the protein-coding genes. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 126 publications
0
0
0
Order By: Relevance
“…Thus, miRNAs may represent promising new targets for developing diagnostic tools for a wide range of infectious disorders. Studies have shown that miRNAs may be employed as biomarkers and biosensors for diagnosing illness [ 145 , 146 ]. ncRNAs larger than 200 nucleotides are long non-coding RNAs (lncRNAs), a diverse class of regulatory RNAs generated by specialized transcriptional units.…”
Section: Advanced Detectionmentioning
confidence: 99%
“…Thus, miRNAs may represent promising new targets for developing diagnostic tools for a wide range of infectious disorders. Studies have shown that miRNAs may be employed as biomarkers and biosensors for diagnosing illness [ 145 , 146 ]. ncRNAs larger than 200 nucleotides are long non-coding RNAs (lncRNAs), a diverse class of regulatory RNAs generated by specialized transcriptional units.…”
Section: Advanced Detectionmentioning
confidence: 99%
“…ncRNAs impact gene expression exerting countless effects on various cellular mechanisms [5]. Dysbalanced expression of ncRNAs may cause numerous human disorders, such as cancer, metabolic syndrome, cardiovascular, autoimmune or infectious diseases [6][7][8][9]. Non-coding regulatory transcripts can be released into the extracellular space and bloodstream within the exosomes which makes them highly stable and resistant to enzymatic degradation.…”
mentioning
confidence: 99%